Waiting for God - Weil, Simone, 1909-1943 (Harper Perennial modern classics., 2009)
"Emerging from the thought-provoking discussions and correspondence Simone Weil had with the Reverend Father Perrin, this classic collection of essays contains the renowned philosopher and social activist's most profound meditations on the relationship of human life to the realm of the transcendent. An enduring masterwork and "one of the most neglected resources of our century" (Adrienne Rich), Waiting for God will continue to influence spiritual and political thought for centuries to come."--Back cover.